Hadith #1023 - Sahih Muslim - Awn bin Abi Juhayfa عون بن أبي جحيفة (Sahih Muslim)
Some of them tried to excel the others (in obtaining water), and in the hadith transmitted by Malik b. Mighwal (the words are): When it was noon, Bilal came out and summoned (people) to (noon) prayer.
Grade: Sahih